PSYCHOLOGICAL FEATURES OF PROFESSIONAL IDENTITY CRISIS EXPERIENCE BY TEACHERS - N. O. Sadovnikova; F. Zannoni (Russian State Vocational Pedagogical University, 2018)
Introduction. In the conditions of constant changes in many public institutions, economic and social instability, permanent educational reforms generate and increase the sense of personal insecurity experienced by modern educators. The requirements of the new social and professional situation involve the independent design of their professional path, the presence of high internal motivation for professional achievement. At the same time, against the backdrop of the low social status of the profession as well as the increasing requirements for the level of performance of activities, many teachers and educators are not prepared to rethink own role in the modern educational process and to resolve emerging professional difficulties. The aim of the publication is to analyze the essence of the concept of "professional identity crisis" and to disclose the psychological features of the experience of this state by teachers. Methodology and research methods. The following questionnaire methods were used for empirical data collection in the course of the study: the method of biographical reflection of M. V. Klementyeva; differential reflexivity test developed by D. A. Leontiev and E. A. Osin; the test of meaningful orientations by D. A. Leontiev. Data processing was conducted by means of descriptive statistics, comparative analysis with the involvement of the Mann-Whitney U test and correlation analysis having applied the Spearman's rank correlation coefficient. Results and scientific novelty. Based on the theoretical analysis of the literature, the authors have defined the term "professional identity crisis experience". The phenomenological questionnaire "Professional Identity Crisis Experience" has been developed. Having used the materials of questioning and self-reports of teachers, the group of the respondents going through the professional personality crisis (n=70) was found out among the examinees (n=150). In the course of the analysis of the results of the pilot research, it was established that there are the following psychological peculiarities experienced by the teachers in the professional crisis: changes in the meanings of the performed activity and revaluation of values; uncertainty of temporal professional perspective (or lack thereof); falling interest in pedagogical activities; lack of self-actualization; frustration; inability to control the events of own life. However, for many teachers, the experience of a professional crisis is accompanied by a reflection of the content of professional activity, the need for reflection of own experiences and states, finding new semantic reference points, perception of own professional prospect. It was found out that most of teachers having experienced the process of crisis as well as those who have never faced it, perceive the life as interesting and full; a crisis state influences only specific parameters of teachers' meaningful orientations which are very important for pedagogical activity. This fact gives evidence of opportunities for successful professional identity crisis overcoming due to updating of vital resources. Practical significance. The results obtained can become the basis for designing the programs of psychological and pedagogical support of teachers' professional development and activity.